Exploring the power of nitric oxide and nanotechnology for prolonging postharvest shelf-life and enhancing fruit quality - Claudiane da Veiga, Julia; Silveira, Neidiquele Maria [UNESP]; Seabra, Amedea Barozzi; Bron, Ilana Urbano (Elsevier, 2024)
Nitric oxide (NO) is a versatile signaling molecule that plays a crucial role in regulating postharvest fruit quality. The utilization of NO donors to elevate endogenous NO levels and induce NO-mediated responses represents a promising strategy for extending fruit shelf-life after harvest. However, the effectiveness of NO treatment is influenced by various factors, including formulation and application methods. In this review, we investigate the impact of NO supply on different fruits, aiming to prolong postharvest shelf-life and enhance fruit quality. Furthermore, we delve into the underlying mechanisms of NO action, particularly its interactions with ethylene and reactive oxygen species (ROS). Excitingly, we also highlight the emerging field of nanotechnology in postharvest applications, discussing the use of nanoparticles as a novel approach for achieving sustained release of NO and enhancing its effects. By harnessing the potential of nanotechnology, our review is a starting point to help identify gaps and future directions in this important, emerging field.
Keywords: Ethylene; Nanomaterials; Oxidative stress; Ripening process